Comparative clinical and phenomenological characteristics of anxiety-depressive disorders of neurotic and organic genesis with sleep disorders. - Лященко, Юлія; Ogorenko Вікторія (Psychosomatic Medicine and General Practice, 2024)
Abstract. Many studies have established a bidirectional relationship between dyssomnia and psychiatric disorders, which confirms the high comorbidity between sleep disorders and anxiety-depressive spectrum disorders. It should be noted that insomnia can be an independent risk factor for anxiety-depressive conditions. Organic pathology of the central nervous system complicates and changes the course and prognosis of mental disorders that have developed against its background. The purpose of this study is to study the clinical and psychopathological features of the leading syndromes in patients with anxiety-depressive disorders of various genesis with sleep disorders. To achieve the goal, 120 patients with anxiety-depressive disorders of various genesis were examined (60 patients with disorders of neurotic genesis and 60 patients with organic genesis). The study was conducted using the clinical-psychopathological method, which was supplemented with the Pittsburgh Sleep Quality Index (PSQI), the insomnia severity index Ch. Morin (ISI), integrative anxiety test (O.P. Bizyuk) (IAT), hospital anxiety and depression scale (HADS), asthenic state scale (ASS) and methods of descriptive and analytical statistics. Results and discussion. When analyzing sleep disorders according to the insomnia severity index, significantly worse indicators of early morning awakening, sleep satisfaction, concern about poor sleep, and quality of life due to poor sleep were established in groups of patients with disorders of organic origin. Also, in these groups, the components of sleep duration, sleep disturbances, frequency of taking sleeping pills according to the Pittsburgh Sleep Quality Index were significantly worse. The integrative anxiety test showed that patients had a statistically significantly higher level of situational anxiety compared to personal anxiety in all observation groups. As for the components of anxiety, for the situational one, it was achieved by an almost equal contribution of the main components (which were within the limits of a high level of expression), except for the component of social reactions of protection with statistically smaller values ​​among all the examined (which corresponded to the average level). In general, patients with anxiety-depressive disorders of organic genesis had significantly higher levels of asthenic and phobic components of situational anxiety and asthenic and phobic components of personal anxiety, which had a high level of expression, as well as the component of social reactions of protection of personal anxiety, which was within the medium level, in compared with groups of patients with disorders of neurotic origin, where the emotional discomfort component of situational anxiety was significantly higher. Patients with disorders of organic genesis had significantly more pronounced asthenic symptoms according to the asthenic state scale. According to the results of the conducted research, clinical and psychopathological features of the leading syndromes of anxiety-depressive disorders of neurotic and organic genesis were established, which helps to approach the treatment of these conditions in a more differentiated manner.